Study guides

☆☆

Q: 3x - 12 equals -2x plus 23 equals?

Write your answer...

Submit

Still have questions?

Related questions

2x +n5y=12

x=5.54x+1= 2x+12-1 -14x=2x+11-2x -2x2x=11/2 /2x=5.5

2x+10=12 2x=2 x=1

2x-12

2x + 7 + 2x = 23 4x + 7 = 23 4x = 16 x = 16/4 x = 4

(4, 5)

2x + 1 = 13; 2x = 12; x = 6

12!

it equals 13X.

2x-3=4x+9 -2x-12=0 2x=-12 x=-6

7x = 21 x = 3

2x + 2 + 5x = 23 2x +5x = 23 -2 7x = 21 X = 3

so 3x + 2 = x + 12 ie 2x = 10 x =5

2x+12-3x = 5 2x-3x = 5-12 -x = -7 x = 7

x would be -3

x=12

x=5

It equals 8x+12

2x + 4 = 16 2x = 16 - 4 2x = 12 x = 12/2 x = 6

Y=4-(2x/3)

(12, 1)

x=1

2x+12-3x = 5 2x-3x = 5-12 x = -7

(3x + 2x) -12 =5x-12 the answer is 5x-12 it is just a simple case of simplifying

They are straight lines.